Percy Bysshe Shelley’s Italian Poems. Flotsam in the Canon, Fragments in a Corpus (Altre Modernità, 2020)
The concept of the literary canon has been extensively debated and questioned as the result of a process of critical negotiation including scholarly discourse as well as editorial and didactic practices. This complex network of cultural, social, and economic factors is also crucial to defining an author’s own canon, that is, the body of works that best identifies a writer’s authorial identity. With specific reference to English Romanticism, Percy Bysshe Shelley’s works represent a relevant case in point, marked as they are by a long and established tradition of textual studies and critical editions. Interestingly, Shelley’s notebooks dating to 1820-1821 include a number of poems and fragments written in Italian, either as original compositions or, more frequently, as attempts at self-translation. Until recently, Shelley’s “Italian corpus” has received only marginal critical attention, viewed as best as a token of his infatuation with Emilia Viviani while he was living in Pisa. This article examines Shelley’s Italian poetic corpus in order to discuss its relevance within his oeuvre, and it argues that these Italian fragments provide significant insights into the poet’s readings and literary models between 1820 and 1821. Moreover, these texts testify to Shelley’s constant exploration of, and engagement with, poetic conventions and poetic discourse. Viewed in this light, such “poetic flotsam” acquires new importance within Shelley’s canon.